Smart Feeding System: Innovation of Timer-Based Automatic Feed Machine in Catfish Cultivation of Wibawamulya MSMEs - Aditama, Reka; Juliandara, Luthpiyah; Qintharah, Yuha Nadhirah; Putra, Purnama (Santoso Academy Network, 2025)
Modern catfish farming increasingly prioritizes the use of sophisticated technology to increase productivity and efficiency. One crucial aspect of catfish farming is the feeding system, which until now is still widely done manually by spreading feed by hand. This conventional method is less efficient, especially on a large scale, because it depends on the timing and dosage of feed, which is often uncontrolled. Inaccuracy in feeding can cause slow fish growth, water pollution due to leftover feed, and an increased risk of cannibalism in fish. To overcome these problems, an automatic feed machine technology equipped with a timer system was developed. This machine can throw feed in a scheduled and controlled manner so that feeding becomes more efficient and optimal. In addition to increasing the efficiency of the work of farmers, the use of automatic feeding machines also contributes to better fish growth and maintains the quality of pond water. The managerial implications that can be suggested are the need to strengthen the institutional capacity and management of women's farmer groups through structured ongoing training, especially in plant cultivation with the Budikdamber system and group financial management.